Changes of leukocyte adherence ability under the influence of magnetic field in the course of a treatment of patients with laryngeal and pharyngeal carcinoma - Čoček, Aleš; Hahn, Aleš; Ambruš, Miloslav; Dohnalová, Alena; Jandová, Anna; Pokorný, Jiří (Electromagnetic biology and medicine, 2008)
The authors were monitoring adherence ability of T lymphocytes in vitro in patients with laryngeal and pharyngeal carcinoma at the presence of tumor-specific and viral LDH antigen. The results were assessed and expressed in percent of non adherent T lymphocytes (NAL). First, NAL in patients before initiating the treatment was compared with NAL control group (voluntary blood donors). The ability of the adherence in T lymphocytes in the control group is statistically significantly higher. Further on, NAL in the course of a successful oncological treatment was monitored at the interval of 6 months following the treatment, and further on at yearly intervals. NAL level drops statistically significantly within 6 months and then hold on at levels with no statistical difference unlike the control group, however, the ability of T lymphocyte in patients to adhere remains statistically significantly lower. Statistically significantly higher levels of NAL are at the presence of LDH viral antigen. Further on, the authors were following the influence of magnetic sinusoidal field of power frequency (50 Hz) of a low induction (0.5, 0.1, and 0.05 mT) on NAL. NAL values under the influence of an experimental magnetic field before initiating the treatment as well as in the course of a successful oncological treatment are statistically significantly lower. It means that magnetic filed increases the adherence ability of T lymphocytes in patients with laryngeal and pharyngeal cancer in vitro.
Keywords: Animals; nádory hltanu; Pharyngeal Neoplasms; buněčná adheze; časové faktory; Time Factors; nádory hlavy a krku; lidé; Laryngeal Neoplasms; Antigens, Viral; Mice; antigeny virové; Cell Adhesion; studie případů a kontrol; myši; leukocyty; nádory hrtanu; Head and Neck Neoplasms; Case-Control Studies; Magnetics; Leukocytes; Lactate dehydrogenase-elevating virus; magnetismus; zvířata; LDH virus; Humans